Análisis de la gestión de residuos aprovechables en la unidad residencial Santiago de Cali: Estudio de caso de ASOBOSUR - Cerón Bernal, Luz Elena (Universidad Antonio Nariño, 2024)
Human activity has always generated an impact on the environment and As communities have become larger and with diverse needs, the evolution of these has been inevitable and necessary. With the development of industry, agriculture, concentration of people in cities, government policies, among others, have problems have arisen for the environment such as greenhouse gases, global warming global, air, sea and land pollution, deforestation, droughts, abusive consumption and the increase in waste (IDEAM, 2007). In response to this problem, in 2015 the member countries of the UN approved the 2030 agenda and Colombia is part of this group of countries that are working to achieve the 17 Sustainable Development Goals (SDGs) (United Nations, 2015